Does “Task Difficulty” Explain “Task-Induced Deactivation?” - Gilbert, Sam; Bird, Geoffrey; Frith, Chris; Burgess, Paul (Frontiers in Psychology, 2012)
The "default mode network" is commonly described as a set of brain regions in which activity is suppressed during relatively demanding, or difficult, tasks. But what sort of tasks are these? We review some of the contrasting ways in which a task might be assessed as being difficult, such as error rate, response time, propensity to interfere with performance of other tasks, and requirement for transformation of internal representations versus accumulation of perceptual information. We then describe a fMRI study in which 18 participants performed two "stimulus-oriented" tasks, where responses were directly cued by visual stimuli, alongside a "stimulus-independent" task, with a greater reliance on internally-generated information. When indexed by response time and error rate, the stimulus-independent task was intermediate in difficulty between the two stimulus-oriented tasks. Nevertheless, BOLD signal in medial rostral prefrontal cortex (MPFC) - a prominent part of the default mode network - was reduced in the stimulus-independent condition in comparison with both the more difficult and the less difficult stimulus-oriented conditions. By contrast, other regions of the default mode network showed greatest deactivation in the difficult stimulus-oriented condition. There was therefore significant functional heterogeneity between different default mode regions. We conclude that task difficulty - as measured by response time and error rate - does not provide an adequate account of signal change in MPFC. At least in some circumstances, a better predictor of MPFC activity is the requirement of a task for transformation and manipulation of internally-represented information, with greatest MPFC activity in situations predominantly requiring attention to perceptual information.